Broadcast journalism : techniques of radio and television news - Boyd, Andrew, 1956-; Stewart, Peter John, 1967-; Alexander, Ray, ....- (Boston (Mass.) : Elsevier, 2008)
A career in broadcast journalism What makes news' Ethics and responsibility News sources Getting the story Conversational writing Newswriting Broadcast style book The interview Setting up the interview From 2-minute headlines to 24-hour news Item selection and order Putting the show together Making the programme fit News anchors and presenters 'On air!' Newsreading mechanics Story treatment Recording Editing The studio The never ending story - the sharing television newsroom Scripting television journalism Gathering television news Camera shots Editing the sound and pictures Going live - live tv reporting in vision Graphics and digital display visuals Presenting television news The television news studio
Keywords: Journalistiek; Radiojournalistiek; Televisiejournalistiek